Kendala Dalam Penyelesaian Kasus Penganiayaan Melalui Penerapan Restorative Justice - Mohammad Rivaldi Lasulika; Fence M. Wantu; Julisa Aprilia Kaluku (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine the position of restorative justice in the criminal justice system in Indonesia and to determine the application of restorative justice in the criminal justice system. This type of research uses empirical legal research, empirical legal research is a legal research method that functions to see the law in real terms and examine how law works in society. The position of restorative justice in the criminal justice system in Indonesia can provide justice that focuses on the needs of the victims, perpetrators of crimes, and also involves community participation, and does not merely fulfill legal provisions or merely impose criminal penalties. In this case, the victim is also involved in the process, while the perpetrator of the crime is also encouraged to take responsibility for his actions, namely by correcting the mistakes he has made. The implementation of restorative justice in the criminal justice system can be seen from various policies and laws and regulations currently in force, but in reality there are inconsistencies between enforcement officials in implementing restorative justice in a case. In fact, many cases ignore restorative justice and result in the criminal being convicted.